The Essence of Indigenous Land Release for Investment Interests - Azis, Yuldiana Zesa (Papua Law Journal, 2017)
The aims of the study were to investigate to what extent the essence of waiver of costumary land in Merauke Regency and to investigate to what extent the release of customary land can provide legal certainty for investors. The research was conducted in Merauke, West Papua Privince. The techniques of obtaining the data were interview and field observations. The data consisted of primary and secondary data. They wereÂ  analyzed using qualitative analysis.The results of the research indicate that the waiver of customary land is the claim of the existence of indigenous people as a condition of the transfer of land rights in Papua Province especially in Merauke Regancy. The release of customary land for investors benefit in Merauke Regency does not provide legal certainty for investors, so it causes the conflict of land affair. The conflict occurs due to the overlapping of tenure or claim by some tribes over the land rights and land boundaries which are not clear because they are natural boundaries.